High-mass dijet cross sections in photoproduction at HERA - Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; et al. (2002)
Dijet differential cross sections for the reaction e+ p → e+ + jet + jet + X in the photoproduction regime have been measured with the ZEUS detector at HERA using an integrated luminosity of 42.7 pb-. The cross sections are given for photon-proton centre-of-mass energies in the range 134 < W < 277 GeV. The differential cross sections as a function of the dijet mass, MJJ, and of the dijet angular variables have been measured for 47 < MJJ < 160 GeV and compared to next-to-leading-order QCD calculations. The dijet events in the region 75 < MJJ < 100 GeV have been used to derive a 95% C.L. upper limit on the cross section for Z0 photoproduction of σ e+p→e+Z0X < 5.9 pb. Upper limits on the photoproduction of new heavy resonances decaying into two jets are also presented for masses in the range between 60 GeV and 155 GeV. © 2002 Elsevier Science B.V. All rights reserved.